Improved hidden Markov modeling for speaker-independent continuous speech recognition - Huang, Xuedong; Alleva, Fil; Hayamizu, Satoru; Hon, Hsiao-Wuen; Hwang, Mei-Yuh; Lee, Kai-Fu (HLT '90 Proceedings of the workshop on Speech and Natural Language, 1990)
The paper reports recent efforts to further improve the performance of the Sphinx system for speaker-independent continuous speech recognition. The recognition error rate is significantly reduced with incorporation of additional dynamic features, semi-continuous hidden Markov models, and speaker clustering. For the June 1990 (RM2) evaluation test set, the error rates of our current system are 4.3% and 19.9% for word-pair grammar and no grammar respectively.